An Integrated Career Coaching and Time-Banking System Promoting Flexibility, Wellness, and Success: A Pilot Program at Stanford University School of Medicine. (June 2018) - Fassiotto, Magali; Simard, Caroline; Sandborg, Christy; Valantine, Hannah; Raymond, Jennifer
Abstract : Faculty in academic medicine experience multiple demands on their time at work and home, which can become a source of stress and dissatisfaction, compromising success. A taskforce convened to diagnose the state of work–life flexibility at Stanford University School of Medicine uncovered two major sources of conflict: work–life conflict, caused by juggling demands of career and home; and work–work conflict, caused by competing priorities of the research, teaching, and clinical missions combined with service and administrative tasks. Using human-centered design research principles, the 2013–2014 Academic Biomedical Career Customization (ABCC) pilot program incorporated two elements to mitigate work–life and work–work conflict: integrated career–life planning, coaching to create a customized plan to meet both career and life goals; and a time-banking system, recognizing behaviors that promote team success with benefits that mitigate work–life and work–work conflicts. A matched-sample pre–post evaluation survey found the two-part program increased perceptions of a culture of flexibility ( P = .020), wellness ( P = .013), understanding of professional development opportunities ( P = .036), and institutional satisfaction ( P = .020) among participants. In addition, analysis of research productivity indicated that over the two-year program, ABCC participants received 1.3 more awards, on average, compared with a matched set of nonparticipants, a funding difference of approximately $1.1 million per person. These results suggest it is possible to mitigate the effects of extreme time pressure on academic medicine faculty, even within existing institutional structures. Abstract : Supplemental Digital Content is available in the text.